Survival of a microbial inoculant in soil after recurrent inoculations - M. Papin; L. Philippot; M. C. Breuil; D. Bru; A. Dreux-Zigha; A. Mounier; X. Le Roux; N. Rouard; A. Spor (Scientific Reports, 2024)
Abstract Microbial inoculants are attracting growing interest in agriculture, but their efficacy remains unreliable in relation to their poor survival, partly due to the competition with the soil resident community. We hypothesised that recurrent inoculation could gradually alleviate this competition and improve the survival of the inoculant while increasing its impact on the resident bacterial community. We tested the effectiveness of such strategy with four inoculation sequences of Pseudomonas fluorescens strain B177 in soil microcosms with increasing number and frequency of inoculation, compared to a non-inoculated control. Each sequence was carried out at two inoculation densities (106 and 108 cfu.g soil−1). The four-inoculation sequence induced a higher abundance of P. fluorescens, 2 weeks after the last inoculation. No impact of inoculation sequences was observed on the resident community diversity and composition. Differential abundance analysis identified only 28 out of 576 dominants OTUs affected by the high-density inoculum, whatever the inoculation sequence. Recurrent inoculations induced a strong accumulation of nitrate, not explained by the abundance of nitrifying or nitrate-reducing microorganisms. In summary, inoculant density rather than inoculation pattern matters for inoculation effect on the resident bacterial communities, while recurrent inoculation allowed to slightly enhance the survival of the inoculant and strongly increased soil nitrate content.